ADVERTISING LAW ENFORCEMENT: COMPARATIVE ANALYSIS OF PROCEDURES AND COMPLIANCE PROGRAM (TSUL LEGAL REPORT, 2026)
The procedure concerning misleading advertisingis started directly by the application of a consumerwho is actually misled by particular advertising.Apart from the consumer application, the proceedingcan be initiated as the result of the administrativemonitoring of the advertising law enforcement.However, the most frequent and effective wayto find a deceptive fact in advertising is throughconsumer application because consumers are ableto recognize deception in its infancy. Eventually,the practice of Advertising law in Uzbekistanstill suffers from a lack of voluntary complianceprograms, which makes co-regulation very weakand enforcement inefficient.